Up-and-coming Radiotracers for Imaging Pain Generators - van der Heijden, Rianne A.; Biswal, Sandip (Seminars in Musculoskeletal Radiology, 2023)
Chronic musculoskeletal pain is among the most highly prevalent diseases worldwide. Managing patients with chronic pain remains very challenging because current imaging techniques focus on morphological causes of pain that can be inaccurate and misleading. Moving away from anatomical constructs of disease, molecular imaging has emerged as a method to identify diseases according to their molecular, physiologic, or cellular signatures that can be applied to the variety of biomolecular changes that occur in nociception and pain processing and therefore have tremendous potential for precisely pinpointing the source of a patient's pain. Several molecular imaging approaches to image the painful process are now available, including imaging of voltage-gated sodium channels, calcium channels, hypermetabolic processes, the substance P receptor, the sigma-1 receptor, and imaging of macrophage trafficking. This article provides an overview of promising molecular imaging approaches for the imaging of musculoskeletal pain with a focus on preclinical methods.
Keywords: pain; inflammation; nociception; molecular imaging; positron emission tomography